Determining the indirect value of a customer - Ryals, Lynette (Westburn Publishers, 2008)
The issue of accountability in marketing has led to a substantial and growing body of work on how to value customer relationships. Net present value methods (customer lifetime value / customer equity) have emerged as generally preferred ways to assess the financial value of customers. However, such calculations fail to take account of other important but indirect sources of value noted by previous researchers, such as advocacy. This paper examines the development and application of three processes to determine indirect value in business-to- business and business-to-consumer contexts. The research shows that indirect value has a measurable monetary impact not captured by conventional financial tools, and that understanding this changes the way in which customers are managed.
Keywords: Customer lifetime value; Customer equity; Indirect value; Advocacy